Manajemen Kepala Sekolah dalam Meningkatkan Program Pembelajaran Siswa di SD Maarif Jogosari Pandaan Pasuruan - Ahmad Miftakhul Choir (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In this research, researchers used a qualitative type of research with a case study approach, with data sources including madrasa heads and other stakeholders. Data collection techniques include interviews, observation and documentation. Meanwhile, the data analysis techniques used consist of data condensation, data presentation, and drawing conclusions. The results of this research are: 1) The management of the principal at SD Maarif Jogosari Pandaan has been running well and according to expectations, this includes planning, organizing, implementing and evaluating or what is usually called POAC (Planning, Organizing, Actuating, Controlling). At the innovative learning program stage, SD Maarif Jogosari Pandaan has two mainstay programs, namely a) Collaboration program with Sahabat Pena, an educational initiative program that involves the exchange of letters between students from different schools. The aim is to improve students' writing and communication skills, broaden their insight into other cultures and environments, and develop empathy and cooperation. b) Manziliyah Program, an educational initiative program that aims to create a learning environment that resembles a family atmosphere at home. This program focuses on developing student character, attitudes and behavior through integrated habituation, coaching and supervision. 2) The obstacles experienced by SD Maarif Jogosari Pandaan in improving learning programs are, a) Lack of socialization and school communication with related parties. b) Lack of support from parents who do not implement these programs at home, such as daily behavioral activities.